Increasing Vocabulary of the Seventh Grade Students of SMPN 6 Bambalamotu Through Realia : Peningkatan Kosakata Siswa Kelas VII SMPN 6 Bambalamotu Melalui Realia - Jenny Yoan Dodowor; Muh. Asri Hente; Ernitasari Mulyadi (Jurnal Kolaboratif Sains, 2023)
The objective of this research was to find out whether the application of realia can increase the students’ vocabulary of especially noun, adjective and verb or not. This research was a pre experimental research design consisting of one group pre-test and post-test. There were two variables of this research. The independent variable was realia and the dependent variable was vocabulary of the seventh grade students of SMP N 6 Bambalamotu. The population of this research was seventh grade students of SMP N 6 Bambalamotu the 2020/2021 academic year. The sample of this research was selected by using total sampling technique and the selected class was grade seven consisting of 20 students. In collecting the data, the researcher conducted pre-test and post-test in order to measure the students’ vocabulary (noun, adjective and verb) before and after applying realia. The researcher analized the data statistically. The result of the test shows that the students’ mean score in the post-test (90,5) was higher than pre-test (30). To find out the significant difference between the pre-test and the post-test, the researcher compared the value of t-counted and t-table by applying 0.05 level of significance for one-tailed test with 19 degree of freedom (20-1=19), the researcher found that the t–table is 1,729. It means that the t-counted (19,139) is higher than the t-table (1,729) and the hypothesis is accepted. The researcher concludes that applying realia can increase the vocabulary of seventh grade students of SMP N 6 Bambalamotu especially noun, adjective and verb. j